FREQUENCY OF MALARIA IN CHILDREN AGED 1-15 YEARS PRESENTING WITH ACUTE FEBRILE ILLNESS AT A TERTIARY CARE HOSPITAL IN PESHAWAR - Munazza Ali; Sumaira Kanwal; Fatima Batool; Roqayya; Samin Ullah Shah (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Acute febrile illness (AFI) is a frequent cause of pediatric hospital visits, with a wide range of underlying etiologies. In malaria-endemic regions like Peshawar, malaria remains a significant and treatable cause of fever in children. Objective: To determine the frequency of malaria among children aged 1–15 years presenting with acute febrile illness at a tertiary care hospital in Peshawar. Study Design: Cross-sectional descriptive study. Setting and Duration: Department of Pediatrics, Hayatabad Medical Complex, Peshawar, from October 21, 2024 to April 28, 2025 Methods: A total of 104 children aged 1 to 15 years presenting with AFI were enrolled through non-probability consecutive sampling. After obtaining informed consent, 5cc of venous blood was drawn under aseptic conditions and tested for malarial parasites using thick and thin blood smear microscopy. Data were analyzed using SPSS version 27. Results: The mean age of participants was 7.22 ± 3.5 years; 52.9% were male and 47.1% female. The average duration of illness was 6.53 ± 2.05 days. A majority of the children belonged to the middle socioeconomic class (48.1%) and lived in urban areas (66.3%). Most parents had at least secondary education (35.6%). Malaria was diagnosed in 23.1% of the children presenting with AFI. Conclusion: Malaria is a prevalent cause of acute febrile illness in children within this population. Early recognition and diagnosis remain crucial in regions where malaria is endemic